Virtual Communities of Practice: do they work, where and why? - Tremblay, Diane-Gabrielle (Organizações & Sociedade, 2014)
This paper highlights various results from a research on communities of practice in Canada, in particular the main conditions and challenges of such new modes of knowledge creation and management. It does this on the basis results to a questionnaire survey administered to the participants of these communities of practice. Participants’ commitment and motivation in the project, dynamism and continuity of leadership, organizational support and recognition of employees’ involvement appear to be the key elements. Some of these variables present interesting differences by age and by gender, and these will be adressed.